Pengembangan Media Kartu Kata Bergambar Kontekstual pada Siswa Kelas I MI Muhammadiyah Lasusua - Nursamsi; Sukmawaty; Edhy Rustan (Socratika: Journal of Progressive Education and Social Inquiry, 2024)
The objectives of this research are: (1) to provide an analysis of the for picture for readiang word card media (2) to describe the steps for developing picture ord card media for reading materials (3) to determine the validity and practicality of picture word card developed in class I MI Muhammadiyah Lasusua. This research uses the Research an Develoment (R&D) type of research. The steps taken in this research are: (1) needs analysis. (2) planning. (3) product development. (4) validity and practicality based on the results of the validity of the picture word card media, it has been validated with categories including design experts getting a percentage score of 68,75% with the valid category. Meanwhile material experts get a percentage score of 68,75% with the valid category. This is a very satisfying and positive result with the fina value obtained and the practical test results being 85,43% with the very practical category based on trial responses with 26 students and an educator, namely a class I teacher, with the finaly value obtained from the practicality beig 94,23% in the very practical category